THE RESPONSE OF SLOVENIAN TEACHERS TO THE MIGRANT CHILDREN FROM FORMER YUGOSLAVIA - Irena Lesar (Dve Domovini, 2005)
The aim of this article is to highlight the situation of the migrant children from former Yugoslavia in primary school in Slovenia. Contemporary school presents teachers with new and relatively high demands which should contribute towards democratisation of relationships and social justice in school. From the aspect of learning outcomes, teachers are required to offer differentiated and individualised lessons which should enable students to acquire as high levels of knowledge as possible. From the developmental aspect, they are required to include all students who should with maximum assistance achieve at least minimal levels of knowledge. Thus, the teacher is expected to be willing to build a class community of individuals who show solidarity and responsibility towards each other, who are able to show respect for and acceptance of difference, and are thus developing their skill to constructively participate in a society of different human beings. We asked ourselves to what extent teachers felt responsible for the migrant children school results and their social inclusion in the class. In regards to the first question, we asked a representative sample of primary school teachers whether factors such as the child’s traits, the situation in the class and the situation at home affect the migrant child’s level of school achievement, and if so, to what extent. In regards to the second question, we tried to establish the role of the child’s parents, the child himself, the other children and their parents, and the teacher in the migrant child’s social inclusion in the class. Results of our study show that Slovenian teachers feel considerably less responsible for achievements of migrant children than for the achievements of other children, and, furthermore, do not feel responsible for migrant children’s successful inclusion in the class. The question therefore is where this feeling of irresponsibility towards migrant children felt by teachers comes from. For this reason, it is necessary to pay utmost attention to making teachers aware of their key role in implementing moral and educational goals of education as well as teaching them to be more sensitive to the real problems of migrant children and to be better prepared for intercultural education.